Divestitures - Emilie R. Feldman; Patia J. McGrath (Journal of Organization Design, 2016)
This article provides an introduction to divestitures and the research streams that examine these deals. Divestitures are defined as the removal of one or more of a company's lines of business via selloff or spinoff. In this article, we describe how research on divestitures has evolved in the finance and strategy literatures, and we explain how to design and conduct empirical research studies on this topic. We also discuss the implications of divestitures for organization design, and outline some directions for future research in this domain.
Keywords: 650; Divestitures; Selloffs; Spinoffs; Corporate scope; Firm boundaries; Corporate strategy